Analisis Kontribusi Emansipasi Perempuan Terhadap PembangunanEkonomi Wilayah Malah Metropolitan Area - Febrianti, Elfera; Arif, Muhammad (Universitas Muhammadiyah Surakarta, 2023)
This study aims to analyse the effect of the Gender Development Index, Gender Empowerment Index, Woman’s Life Expectancy, and AverageLeght of Schoolling for Woman on Gross Regional Domestic Product in the Malang Metropolitan Area in 2016-2020. The study uses secondary date inform of panel data (a combination of time series date and cross section date), which are observations from 8 regenties/cities in the Malang Metropolitan Area. The date obtained comes from the Central Statistics Agency. The result of the analysis show that the Gender Development Index has a negative effect on the Gross Regional Domestic Product andthe Woman’s Life Expectancy has a positive effect on the Gross Regional Domestic Product. Meanwhile, the Gender Empowerment Index andthe Average Leght of Schooling for woman have no effect on the Gross Regional Domestic Product in the Malang Metropolitan Area in 2016-2020